Expression of circadian clock genes and diurnal oscillations of key physiological events in response to AsV and AsIII in soybean plants - Vezza, Mariana Elisa (2020)
Soybean (Glycine max L.) is often cultivated in soils with a high content of arsenic (As). Since this greatly affects crop growth and yield, the response mechanisms underlying tolerance to As should be well understood. Circadian rhythms are known to play a central role in plant adaptation to stressful conditions. Therefore, our aim was to evaluate the effects of arseniate (AsV) and arsenite (AsIII) on the expression of key circadian clock genes (CG) and on the possible diurnal oscillation of physiological events induced by As in soybean plants. Leaves and roots were evaluated during light-dark phases at 4-h intervals. The changes caused by As in the expression profiles of all CGs analyzed depended on its chemical form and the plant organ involved. Overexpression of GmLCL1, GmTOC1, GmPRR9 and GmGI was observed in leaves mainly upon AsV-treatment, while underexpression of GmLCL1 and overexpression of GmPRR9, GmELF4 and GmGI occurred in roots, mainly upon AsIII-treatment. Moreover, As seemed to have an influence on the daily fluctuations observed in events triggered in response to the stress, such as stomatal aperture control, phytochelatin (PC) and glutathione (GSH) content, and total antioxidant, ascorbate (APx) and glutathione peroxidase (GPx) activities. In particular, the increase in the synthesis of PCs (the main As chelators) and the decrease in their precursor, GSH, were higher during the light phase, while APx and GPx activities increased during the dark phase in As-treated plants. The results suggest a link between the circadian clock and the response to As in soybean plants, since exposure to As modified CG expression and induced important changes in the diurnal oscillation of several As-response mechanisms. Circadian clock regulation, then, might play a vital role in the tolerance to As.